Low Methoxyl Pectin Protects against Autoimmune Diabetes and Associated Caecal Dysfunction. Issue 21 (5th September 2019) - Wu, Chengfei; Pan, Li‐Long; Luo, Yang; Niu, Wenying; Fang, Xin; Liang, Wenjie; Li, Jiahong; Li, Hongli; Pan, Xiaohua; Yang, Guilian; Chen, Wei; Zhang, Hao; et al.
Abstract : Scope: This study aims to examine the protective effects of specific low‐methoxyl pectin (LMP) on the development of type 1 diabetes (T1D). Methods and results: Female non‐obese diabetic (NOD) mice are weaned onto either control or 5% LMP supplemented diets for up to 22 weeks of age. T1D incidence, gut barrier function, and pancreatic‐gut immune responses are analyzed. LMP supplementation significantly dampened the onset of T1D in NOD mice. LMP supplementation induces caecal homeostasis, as indicated by the increasing SCFAs production, higher expression of tight junction proteins claudin 1, zonula occludens‐2 in caecum. Furthermore, LMP‐mediated caecal homeostasis impacts gut‐pancreatic immunity, as evidenced by increased regulatory T cell population, modulated inflammatory cytokine expression, and suppressed NOD like receptor protein 3 (NLRP3) inflammasome activation in both caecum and pancreas. Conclusion: The data demonstrate that LMP limits T1D development by inducing caecal homeostasis to shape pancreatic immune environment, providing a scientific basis for using LMP as a novel functional supplementation to intervene T1D. Abstract : A proposed model depicting the mechanism by which LMP (low methoxyl pectin) protects against T1D and associated caecal homeostasis is presented. LMP maintains gut immune and barrier homeostasis to shape the pancreatic immune environment, hereby mitigating the development of T1D in non‐obese diabetic (NOD) mice.